2018
DOI: 10.1017/s2045796018000239
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of cannabidiol in the treatment of psychiatric disorders: a critical overview

Abstract: This Section of Epidemiology and Psychiatric Sciences appears in each issue of the Journal to stress the relevance of epidemiology for behavioral neurosciences, reporting the results of studies that explore the use of an epidemiological approach to provide a better understanding of the neural basis of major psychiatric disorders and, in turn, the utilisation of the behavioural neurosciences for promoting innovative epidemiological research.The ultimate aim is to help the translation of most relevant research f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 31 publications
0
42
0
1
Order By: Relevance
“…Additionally, a 2018 neuroimaging study examining patients at high risk of psychosis showed that CBD normalized fMRI signatures in regions associated with psychosis [52]. Other preclinical work has suggested several mechanisms through which CBD may exert anti-psychotic properties, including antagonism of CB1 receptors, modulation of dopamine signaling, and decreasing neuroinflammation [53,54]. Follow-up RCTs examining the effectiveness of CBD in psychotic disorders has shown mixed results [54].…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a 2018 neuroimaging study examining patients at high risk of psychosis showed that CBD normalized fMRI signatures in regions associated with psychosis [52]. Other preclinical work has suggested several mechanisms through which CBD may exert anti-psychotic properties, including antagonism of CB1 receptors, modulation of dopamine signaling, and decreasing neuroinflammation [53,54]. Follow-up RCTs examining the effectiveness of CBD in psychotic disorders has shown mixed results [54].…”
Section: Indicationsmentioning
confidence: 99%
“…Other preclinical work has suggested several mechanisms through which CBD may exert anti-psychotic properties, including antagonism of CB1 receptors, modulation of dopamine signaling, and decreasing neuroinflammation [53,54]. Follow-up RCTs examining the effectiveness of CBD in psychotic disorders has shown mixed results [54]. A 2012 double-blind RCT reported that CBD was as effective as amisulpride, an antipsychotic commonly used to treat schizophrenia, in treating both positive and negative symptoms of schizophrenia and had fewer associated side effects, including extrapyramidal symptoms, hyperprolactinemia, and weight gain [55].…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In vitro, animal, and human studies suggest mechanisms of action for CBD directly or tangentially related to the endocannabinoid system, as delineated in Table 1. [2][3][4][5][6][7][8][9][10] There has been an incredible amount of media coverage on the health benefits of CBD, with CBD products heralded as medical breakthroughs or even miracles for all types of diseases. 11,12 Medical professionals may be interested in CBD as a new therapy for patients with limited traditional options or are asked about CBD products by patients, family, and acquaintances for a host of ailments.…”
mentioning
confidence: 99%
“…Treatment options are limited and a better understanding of the brain mechanisms involved might lead to novel treatments. Although THC in particular has been implicated in the development of psychosis or schizophrenia [6,7], several recent reviews have suggested that CBD may be beneficial in a number of psychiatric disorders including psychosis [8][9][10]. However, there is substantial variability in experimental power, methodology, dosing and experimental protocols used, and the mechanism of any antipsychotic-like effect of CBD remains unclear.…”
Section: Introductionmentioning
confidence: 99%